2013
DOI: 10.1136/heartjnl-2012-303465
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of training mode, imaging modality and body size influences on the morphology and function of the male athlete's heart

Abstract: Morphological features of the male AH were noted in both athlete groups. A training-specific pattern of concentric hypertrophy was not discerned in resistance athletes. Both imaging mode and BSA can have a significant impact on the interpretation of AH data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

26
186
3
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(222 citation statements)
references
References 40 publications
(32 reference statements)
26
186
3
7
Order By: Relevance
“…There were no differences in the wall thickness between those groups. The same results were presented in the above-mentioned meta-analysis by Utomi et al [9], in which the authors, contrary to the previous meta-analysis, concluded that the training-specific pattern of concentric hypertrophy was not discerned in the resistance athletes.…”
Section: Left Ventricular Hypertrophycontrasting
confidence: 53%
See 3 more Smart Citations
“…There were no differences in the wall thickness between those groups. The same results were presented in the above-mentioned meta-analysis by Utomi et al [9], in which the authors, contrary to the previous meta-analysis, concluded that the training-specific pattern of concentric hypertrophy was not discerned in the resistance athletes.…”
Section: Left Ventricular Hypertrophycontrasting
confidence: 53%
“…Nevertheless, unambiguously, athletes who are engaged in physical training have a greater LVWT and LVEDD, compared to the non-athletic population, and endurance athletes have the biggest hearts -those practicing rowing, cross-country skiing, cycling, and long-distance running. The aforementioned meta-analyses confirm this unequivocally [8,9]. Athletes also have proportionally larger left atria (LA) and right ventricles (RV), and this reflects a balanced cardiac remodelling process [9][10][11][12].…”
Section: Left Ventricular Hypertrophysupporting
confidence: 52%
See 2 more Smart Citations
“…Обсуждение В систематическом обзоре (2013), в который были включены проспективные исследования с участием элитных молодых спортсменов мужского пола и муж-чин, ведущих малоподвижный образ жизни [8], приво-дятся сравнительные данные параметров сердца послед-них. По данным настоящего обзора, все параметры левого желудочка были выше в группе спорт сменов.…”
unclassified